Fibronectin Adherent Cell Populations Derived From Avascular and Vascular Regions of the Meniscus Have Enhanced Clonogenicity and Differentiation Potential Under Physioxia - Pattappa, Girish; Reischl, Franziska; Jahns, Judith; Schewior, Ruth; Lang, Siegmund; Zellner, Johannes; Johnstone, Brian; Docheva, Denitsa; Angele, Peter (Frontiers in Bioengineering and Biotechnology, 2022)
The meniscus is composed of an avascular inner region and vascular outer region. The vascular region has been shown to contain a progenitor population with multilineage differentiation capacity. Strategies facilitating the isolation and propagation of these progenitors can be used to develop cell-based meniscal therapies. Differential adhesion to fibronectin has been used to isolate progenitor populations from cartilage, while low oxygen or physioxia (2% oxygen) enhances the meniscal phenotype. This study aimed to isolate progenitor populations from the avascular and vascular meniscus using differential fibronectin adherence and examine their clonogenicity and differentiation potential under hyperoxia (20% oxygen) and physioxia (2% oxygen). Human vascular and avascular meniscus cells were seeded onto fibronectin-coated dishes for a short period and monitored for colony formation under either hyperoxia or physioxia. Non-fibronectin adherent meniscus cells were also expanded under both oxygen tension. Individual fibronectin adherent colonies were isolated and further expanded, until approximately ten population doublings (passage 3), whereby they underwent chondrogenic, osteogenic, and adipogenic differentiation. Physioxia enhances clonogenicity of vascular and avascular meniscus cells on plastic or fibronectin-coated plates. Combined differential fibronectin adhesion and physioxia isolated a progenitor population from both meniscus regions with trilineage differentiation potential compared to equivalent hyperoxia progenitors. Physioxia isolated progenitors had a significantly enhanced meniscus matrix content without the presence of collagen X. These results demonstrate that combined physioxia and fibronectin adherence can isolate and propagate a meniscus progenitor population that can potentially be used to treat meniscal tears or defects.